Network pharmacology and UHPLC-HRMS reveal the mechanism of QSFZYL and BMSCs overexpressing IFN-γ against lung adenocarcinoma - Lv, Zhen; Liu, MingXuan; Yang, YingYing; Xie, YaHui; Tian, YiHong; Xu, XiangNing; Wang, YinDi; Wei, XingMing; Ma, DongJing; Tian, XueJiao; Wu, JianJun (Frontiers in Immunology, 2025)
BackgroundLung cancer is a significant public health concern in China, posing a serious threat to the population. The QiShenFuZhengYiLiu (QSFZYL) is commonly prescribed as a complementary treatment for cancer patients, although its anticancer mechanism remains unclear. The purpose of this study was to explore the therapeutic mechanisms of QSFZYL in lung adenocarcinoma (LUAD).MethodsThe mechanism of QSFZYL for treating LUAD was analyzed using comprehensive network pharmacology and UHPLC-HRMS, combined with experimental validation (in vivo).ResultsNetwork pharmacology analysis suggested that the therapeutic effects of QSFZYL on LUAD may involve the JAK/STAT signaling pathway. UHPLC-HRMS identified 26 differential components, with representative compounds including astragalus lysine alkaloids, monoterpenoids, isoflavonoids, and flavonoids. In vivo experiments demonstrated that QSFZYL combined with IFN-γ significantly inhibited LUAD growth and promoted infiltration of CD3 and CD8 T cell, and downregulated JAK2, STAT3, and PD-L1 expression, promoted apoptosis.ConclusionQSFZY combined with IFN-γ overexpressing BMSCs effectively inhibit LUAD progression. The primary mechanisms include the suppression of cancer cell growth, promotion of apoptosis and infiltration of CD3 and CD8 T cells, and inhibition of the JAK2/STAT3 signaling pathway, and downregulated PD-L1 expression.